2020
DOI: 10.1055/a-1149-1862
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of bariatric endoscopic procedures in the treatment of morbid obesity: a systematic review and network meta-analysis

Abstract: Background The comparative efficacy of bariatric endoscopic procedures has not been completely elucidated. We aimed to comprehensively evaluate the efficacy of bariatric endoscopic procedures. Methods We searched for randomized controlled trials investigating the efficacy of bariatric endoscopic procedures, including the use of an intragastric balloon, duodenal-jejunal bypass liner (DJBL), aspiration therapy, primary obesity surgery endoluminal (POSE) procedure, and botulinum toxin injection to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
5
1
2
Order By: Relevance
“…3 이 중 가장 먼저 시 작된 방법은 위풍선 삽입술로, 4 현재 미국이나 유럽에서 활발하 게 시행되고 있고 단기간의 체중 감량 효과가 입증되었다. [4][5][6][7] 최근 국내에서도 내시경을 통한 위풍선 삽입술의 시행 횟수 가 점차 증가하고 있으나 8,9 위풍선을 제거한 후에도 감소된 체 중이 유지되는지는 명확하지 않고, 관련된 연구 역시 부족하 다. 10…”
Section: 서 론unclassified
“…3 이 중 가장 먼저 시 작된 방법은 위풍선 삽입술로, 4 현재 미국이나 유럽에서 활발하 게 시행되고 있고 단기간의 체중 감량 효과가 입증되었다. [4][5][6][7] 최근 국내에서도 내시경을 통한 위풍선 삽입술의 시행 횟수 가 점차 증가하고 있으나 8,9 위풍선을 제거한 후에도 감소된 체 중이 유지되는지는 명확하지 않고, 관련된 연구 역시 부족하 다. 10…”
Section: 서 론unclassified
“…In recent years, endoscopic bariatric and metabolic therapies (EBMTs) have emerged as less invasive methods targeted to achieve comparable results to bariatric surgery for obesity and its metabolic comorbidities at a more affordable cost and a lower risk of complications (8). Currently, six bariatric and metabolicendoscopy devices have been approved by the US Food and Drug Administration (FDA): Orbera Intragastric Balloon System (IGB; Apollo Endosurgery, Austin, TX, USA), Obalon Balloon System (Obalon Therapeutics, Carlsbad, CA, USA), transpyloric shuttle (TPS; BAROnova, San Carlos, CA, USA), OverStitch Endoscopic Suturing System (Apollo Endosurgery) for endoscopic sleeve gastroplasty (ESG), incisionless operating platform (IOP; USGI Medical, San Clemente, CA, USA) for primary obesity surgery endoluminal (POSE), and AspireAssist (Aspire Bariatrics, King of Prussia, PA, USA) for aspiration therapy (AT).…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy in terms of weight loss achieved is around 10-25%. Previous studies have demonstrated that long-term total body weight reduction by 5-10% is sufficient to achieve a significant decrease in the risk of a cardiovascular event or type 2 DM [14,15].…”
Section: Introductionmentioning
confidence: 99%